Compatibility and conductivity of LiClO4 free and doped polyacrylate-poly(ethylene oxide)blends - Sim, L.H.; Gan, S.N.; Chan, C.H.; Kammer, H.W.; Yahya, R. (2009)
Thermal behaviour of polyacrylate (PAc)/poly(ethylene oxide) (PEO) and PAc/PEO doped with LiClO4 were investigated by differential scanning calorimetry. The constituents, PAc and PEO, show immiscibility after glass transition temperature Tg analysis. The addition of LiClO4 increases the Tg's of neat PAc, PEO and their blends. The conductivities at 30Â°C of PAc, PAc/PEO 40 : 60 doped with 15 wt- LiClO 4 and PEO are 8.3Ã10-10, 1.2Ã10-6 and 7.9Ã10-6 S cm-1 respectively. Reasonably high conductivity of the PAc/PEO/LiClO4 blends makes it a potential polymer electrolyte.